The Internal Political and Economic Situation in the Hashemite Kingdom of Jordan 1988-1996 - AL-Tikrity, Harith A.; Daham, Ayad Khalaf (Journal of Tikrit University for Humanities, 2022)
The Hashemite Kingdom of Jordan has gone through different historical stages that are completely related to its economic reality, and its dependence on international and regional aid. As such, the researcher tried to delve into the presentation of the political and economic events that the Kingdom went through in an attempt to understand the overlapping and interdependence between the two sides and try to answer many of the questions that afflicted the political life that as long as the successive ministries changed. The topic has been presented to more than one axis. While the first deals with local and regional reflections and their impact on the conduct of the 1989 elections, the second axis is devoted to the study of the economic correction program. The third axis presents the obstacles and elements of economic policies. The fourth axis discusses international and regional conferences and their repercussions On the internal situation 1994-1996. The fifth deals with the economic crisis in 1996.